Effect of a comprehensive eRehabilitation intervention alongside conventional stroke rehabilitation on disability and health-related quality of life: A pre-post comparison - Berber Brouns; Leti van Bodegom-Vos; Arend J. de Kloet; Sietske J. Tamminga; Gerard Volker; Monique A.M. Berger; Marta Fiocco; Paulien H. Goossens; Thea P.M Vlieland; Jorit J.L. Meesters (Medical Journals Sweden, 2021)
Objective: To compare the effect on disability and quality of life, of conventional rehabilitation (control group) with individualized, tailored eRehabilitation intervention alongside conventional rehabilitation (Fast@home; intervention group), for people with stroke. Methods: Pre-post design. The intervention comprised cognitive (Braingymmer®) and physical (Telerevalidatie®/Physitrack®) exercises, activity-tracking (Activ8®) and psycho-education. Assessments were made at admission (T0) and after 3 (T3) and 6 months (T6). The primary outcome concerned disability (Stroke Impact Scale; SIS). Secondary outcomes were: health-related quality of life, fatigue, self-management, participation and physical activity. Changes in scores between T0-T3, T3-T6, and T0-T6 were compared by analysis of variance and linear mixed models. Results: The study included 153 and 165 people with stroke in the control and intervention groups, respectively. In the intervention group, 82 (50%) people received the intervention, of whom 54 (66%) used it. Between T3 and T6, the change in scores for the SIS subscales Communication (control group/intervention group -1.7/-0.3) and Physical strength (-5.7/3.3) were significantly greater in the total intervention group (all mean differences< minimally clinically important differences). No significant differences were found for other SIS subscales or secondary outcomes, or between T0-T3 and T0-T6. Conclusion: eRehabilitation alongside conventional stroke rehabilitation had a small positive effect on communication and physical strength on the longer term, compared to conventional rehabilitation only.